Outcome-Based Education in the 21st Century: Innovations, Implementation and Impact - Edwin; Susanta, Vonny A. (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to evaluate the development of Outcome-Based Education (OBE) in the 21st century through a Systematic Literature Review of 38 scholarly articles selected based on PRISMA guidelines. The findings indicate that OBE innovations include integrating cutting-edge technologies such as artificial intelligence, flipped classrooms, and blended learning models, which have been shown to enhance student engagement and learning outcomes. Globally, the implementation of OBE occurs through various approaches, such as the BOPPPS model, CDIO, and personalized algorithm-based learning. The impact of OBE includes improvements in critical thinking skills, communication, student satisfaction, and the employability of graduates in the job market. However, significant challenges remain, such as faculty resistance, limitations in professional training, and a lack of long-term evaluation. The study concludes that OBE holds substantial potential as an innovative framework in higher education if applied contextually and sustainably, with recommendations for future research focusing on long-term sustainability, inclusivity, and cross-cultural adaptability.